Evaluate The Commitment Of The Central Organization For Financial Control (COFC) To Performance Control According To The Standards 3000 Of INTOSAI A Field Study In The Branch Of COFC In Lattakia - لمى , اسبر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed at evaluating Commitment of the Central Organization for Financial Control (COFC) to Performance Control According to The Standards 3000 of Supreme Audit Institutions (INTOSAI) in Syria, the descriptive analytical method was followed, and a questionnaire was distributed to a sample of technical workers in COFC branch in Lattakia, 43 valid questionnaires were analyzed by SPSS 23. The research reached that the inspectors of the COFC/Lattakia branch/, are auditing according to (INTOSAI) 3000 standards related to performance control, the average of the studied sample was 3.2379, and the inspectors of the COFC are committed with a large extent to the dimensions of economy, efficiency and effectiveness. The research recommended: the necessity for continuous improvement of the controlling work carried out by the COFC through updating the approved standards, preparing qualified inspectors who are able to understand all performance control standards, the necessity for specialized training courses, especially on the concept of benchmarking.